Magnetic cavitation and the reemergence of nonlocal transport in laser plasmas. - Ridgers, C; Kingham, R; Thomas, A (2008)
We present the first fully kinetic Vlasov-Fokker-Planck simulations of nanosecond laser-plasma interactions including self-consistent magnetic fields and hydrodynamic plasma expansion. For the largest magnetic fields externally applied to long-pulse laser-gas-jet experiments (12 T) a significant degree of cavitation of the B field (>40%) will be shown to occur from the laser-heated region in under half a nanosecond. This is due to the Nernst effect and leads to the reemergence of nonlocality even if the initial value of the magnetic field strength is sufficient to localize the transport.